2014
DOI: 10.4085/1062-6050-49.3.28
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Neuromuscular Control at the Knee in Individuals With Chronic Ankle Instability

Abstract: Context: Few authors have assessed neuromuscular kneestabilization strategies in individuals with chronic ankle instability (CAI) during functional activities.Objective: To investigate the influence of CAI on neuromuscular characteristics around the knee during a stop-jump task.Design: Case-control study. Setting: Research laboratory. Participants or Other Participants: A total of 19 participants with self-reported unilateral CAI and 19 healthy control participants volunteered for this study.Intervention(s): P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 40 publications
(63 reference statements)
1
31
1
Order By: Relevance
“…Numerous researchers have reported the mechanical, [3][4][5][6] sensory, [7][8][9] and proximal changes [12][13][14][15] that occur after an ankle sprain and in those with CAI. Any of these negative alterations could lead to decreased physical activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous researchers have reported the mechanical, [3][4][5][6] sensory, [7][8][9] and proximal changes [12][13][14][15] that occur after an ankle sprain and in those with CAI. Any of these negative alterations could lead to decreased physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups [12][13][14][15][16] have reported alterations in kneejoint kinematics, neuromuscular control, and knee torque production in those with CAI. Most recently, Terada et al 12 demonstrated altered feed-forward patterns of the vastus medialis oblique (VMO) muscle in those with CAI.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Sensorimotor mechanisms are largely responsible for maintaining joint homeostasis, including proper landing technique and dynamic stability (Riemann & Lephart, 2002). Although it has been reported that participants with CAI exhibit sensorimotor alterations during performance of dynamic stability tasks (Brown, Bowser, & Simpson, 2012;Caulfield & Garrett, 2002;Gribble & Robinson, 2009Hass, Bishop, Doidge, & Wikstrom, 2010;Terada, Pietrosimone, & Gribble, 2014), the underlying sensorimotor mechanisms associated with disability in CAI patients still remain unknown.…”
Section: Introductionmentioning
confidence: 96%